Influence of chromium concentration on the electron magnetic resonance linewidth of Cr3+ in SrTiO3 - de Biasi,Ronaldo Sergio (2012)
Electron magnetic resonance (EMR) spectra of Cr3+ ions in samples of chromium-doped strontium titanate (SrTiO3) have been studied at room temperature for chromium concentrations between 0.20 and 1.00 mol%. According to previous studies, chromium substitutes Ti4+ sites in the lattice and its preferred valence state is Cr4+, which is EMR silent in the X-band, but the trivalent state can be produced by illumination or codoping with Nb. In the present work, the codoping method was used; the results show the electron magnetic resonance linewidth of the Cr3+ spectrum increases with increasing chromium concentration and that the range of the exchange interaction between Cr3+ ions is about 0.96 nm.